2023
DOI: 10.1007/s00406-023-01571-4
|View full text |Cite
|
Sign up to set email alerts
|

Esmethadone-HCl (REL-1017): a promising rapid antidepressant

Abstract: This review article presents select recent studies that form the basis for the development of esmethadone into a potential new drug. Esmethadone is a promising member of the pharmacological class of uncompetitive N-methyl-D-aspartate receptor (NMDAR) antagonists that have shown efficacy for major depressive disorder (MDD) and other diseases and disorders, such as Alzheimer’s dementia and pseudobulbar affect. The other drugs in the novel class of NMDAR antagonists with therapeutic uses that are discussed for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Rel-1017, another NMDAR antagonist, demonstrated rapid efficacy in MDD, with the persistence of antidepressant activity up to 1 week after treatment discontinuation (Fava et al, 2022). Additionally, changes in anhedonia, motivation, and reward have accompanied antidepressant-like activity in rodent models, after a single dose (Fogaça et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rel-1017, another NMDAR antagonist, demonstrated rapid efficacy in MDD, with the persistence of antidepressant activity up to 1 week after treatment discontinuation (Fava et al, 2022). Additionally, changes in anhedonia, motivation, and reward have accompanied antidepressant-like activity in rodent models, after a single dose (Fogaça et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the antidepressant effect extended also to an enhancement in cognitive and social functioning, anxiety, agitation, anger, irritability, and sleep quality. It also showed a favorable safety profile, characterized by dose-related nausea and somnolence only at higher doses [ 30 - 33 ]. It therefore received the FDA fast-track designation as an adjunctive treatment for major depression disorder.…”
Section: Dextromethadonementioning
confidence: 99%
“…Another trial explored the use of adjunctive esmethadone, another uncompetitive NMDA receptor antagonist [154]. This trial demonstrated rapid and robust reductions in depressive symptoms, although this was not consistently replicated in a subsequent phase 3 trial.…”
Section: Antidepressant Breakthroughs: Advancements In Pharmacotherap...mentioning
confidence: 99%